Comparing the Court and Medical Interpreters in the USA: the certification process. - Zervaki, Thei (International Journal of Language, Translation and Intercultural Communication, 2016)
The scope of the paper is to provide information on the current Court and Medical Interpreting certification process in the USA. It includes information on the administrative aspects of certification for both Courts and Healthcare institutions. In the United States of America, the term Community Interpreting is not commonly used. There are two major types of interpretation: Court and Medical. The first is offered in US State and Federal courts to all LEP clients; the second is offered to the Healthcare Institutions as hospitals, healthcare centers and clinics to name a few. As the space is limited for this authoring, the paper won’t include data and statistics from different states that showcase and document success and failure rates of the certification examinations. This may well be the topic of a different paper. This paper does not include information on the Court Interpreting for the Deaf and Hard of Hearing.